Study on real-time media congestion avoidance technique for video streaming over wireless local area network - C Mohanapriya; J Govindarajan (Institute of Advanced Engineering and Science, 2019)
The video streaming is one of the important application which consumes more bandwidth compared to non-real-time traffic. Most of the existing video transmissions are either using UDP or RTP over UDP. Since these protocols are not designed with congestion control, they affect the performance of peer video transmissions and the non-real-time applications. Like TFRC, Real-Time Media Congestion Avoidance (RMCAT) is one of the recently proposed frameworks to provide congestion control for real-time applications. Since the need for video transmission is increasing over the wireless LAN, in this paper the performance of the protocol was studied over WLAN with different network conditions. From the detailed study, we observed that RMCAT considers the packet losses due to the distance and channel conditions as congestion loss, and hence it reduced the sending rate thereby it affected the video transmission.